Efecto de la temperatura sobre el desarrollo y la actividad patogenica de Corticium sasakii (Shirai) Matsumoto - Camara, M.=700 1 Herrera Isla, M.; Galantai, E.
(En, Es)
ilus., 7 ref.
Keywords: CORTICIUM; TEMPERATURA DEL AIRE; CRECIMIENTO; MORFOLOGIA FUNGICA; PATOGENESIS; CUBA; CORTICIUM SASAKII